Patient characteristics and cardiac surgical outcomes at a tertiary care hospital in Kenya, 2008–2017: a retrospective study - Chavez-Lindell, Tamara; Kikwe, Bob; Gikonyo, Anthony; Odoi, Agricola (PeerJ, 2021)
Background Cardiac surgeries are high risk procedures that require specialized care and access to these procedures is often limited in resource-poor countries. Although fatalities for surgical patients across Africa are twice that of the global rate, cardiac surgical mortality continent-wide is only slightly higher than all-surgical mortality. Understanding demographic and health characteristics of patients and the associations of these characteristics with morbidity and mortality events is important in guiding care decisions. Therefore, the objectives of this study were to: (a) describe the characteristics of cardiac surgical patients; (b) identify the associations between these characteristics and morbidity and mortality events following cardiac surgery. Methods Patient characteristics and post-surgical complications were abstracted for all cardiac surgical patients treated at a tertiary care hospital in Kenya from 2008 to 2017. Descriptive analyses of demographic factors, co-morbidities, peri-operative conditions, and post-surgical complications were conducted for adult and pediatric patients. Cochran-Armitage trend test was used to assess temporal trends in risk of death. Multivariable ordinary logistic and Firth logistic models were used to investigate predictors of surgical outcomes. Results The study included a total of 181 patients (150 adult and 31 pediatric patients). Most (91.3%) adult patients had acquired conditions while 45.2% of the pediatric patients had congenital defects. Adult patients tended to have co-morbid conditions including hypertension (16.7%), diabetes mellitus (7.3%), and nephropathy (6.7%). Most patients (76.0% adults and 96.8% pediatric patients) underwent ≤ 2 surgical procedures during their hospital stay. Seventy percent of adult and 54.8% of the pediatric patients experienced at least one post-surgical complication including mediastinal hemorrhage, acute kidney injury and death. Patient characteristics played the greatest roles in predicting post-surgical complications. For adult patients, significant predictors of acute kidney injury included atrial fibrillation (OR = 18.25; p = .001), mitral valve replacement (OR = 0.14; p = .019), and use of cardiopulmonary bypass (OR = 0.06; p = .002). Significant predictors of 30-day mortality were age (OR = 1.05; p = .015) and atrial fibrillation (OR = 4.12, p = .018). Although the number of surgeries increased over the decade-long study period, there were no significant (p = .467) temporal trends in the risk of death. Conclusions Awareness of demographic and peri-surgical factors that are predictors of complications is useful in guiding clinical decisions to reduce morbidity and mortality. Identification of co-morbidities as the most useful predictors of post-surgical complications suggests that patient characteristics may be a larger contributor to the incidence of complications than surgical practices.
Keywords: Patient characteristics; Open heart surgery; Kenya; Cardiothoracic surgical outcomes; Firth logistic regression model; Cardiac surgery; 30-day mortality; In-hospital mortality; Intra-surgical mortality; Out-of-hospital mortality